ERAP, KIR, and HLA-C Profile in Recurrent Implantation Failure - Piekarska, Karolina; Radwan, Paweł; Tarnowska, Agnieszka; Wiśniewski, Andrzej; Radwan, Michał; Wilczyński, Jacek R.; Malinowski, Andrzej; Nowak, Izabela (Frontiers in Immunology, 2021)
The mother's uterine immune system is dominated by uterine NK cells during the first trimester of pregnancy. These cells express killer cell immunoglobulin-like receptors (KIR) of inhibitory or activating function. Invading extravillous trophoblast cells express HLA-C molecules and both maternal and paternal HLA-C allotypes are presented to KIRs. Endoplasmic reticulum aminopeptidase 1 (ERAP1) and ERAP2 shape the HLA class I immunopeptidome. The ERAPs remove N-terminal residues from antigenic precursor peptides and generate optimal-length peptides to fit into the HLA class I groove. The inability to form the correct HLA class I complexes with the appropriate peptides may result in a lack of immune response by NK cells. The aim of this study was to investigate the role of ERAP1 and ERAP2 polymorphisms in the context of KIR and HLA-C genes in recurrent implantation failure (RIF). In addition, for the first time, we showed the results of ERAP1 and ERAP2 secretion into the peripheral blood of patients and fertile women. We tested a total of 881 women. 496 females were patients who, together with their partners, participated in in vitro fertilization (IVF). A group of 385 fertile women constituted the control group. Women positive for KIR genes in Tel AA region and HLA-C2C2 were more prevalent in the RIF group than in fertile women (p/pcorr. = 0.004/0.012, OR = 2.321). Of the ERAP polymorphisms studied, two of them (rs26653 and rs26618) appear to affect RIF susceptibility in HLA-C2 positive patients. Moreover, fertile women who gave birth in the past, secreted significantly more ERAP1 than IVF women and pregnant women (p < 0.0001 and p = 0.0005, respectively). In the case of ERAP2, the opposite result was observed; i.e., fertile women secreted far less ERAP2 than IVF patients (p = 0.0098). Patients who became pregnant after IVF-ET released far less ERAP2 than patients who miscarried (p = 0.0032). ROC analyses indicate a value of about 2.9 ng/mL ERAP2 as a point of differentiation between patients who miscarried from those who gave birth to a healthy child. Our study indicates that both ERAP1 and ERAP2 may be involved in processes related to reproduction.